Clinical significance of mitochondrial DNA content in acute promyelocytic leukaemia. (20th October 2022) - Pereira‐Martins, Diego A.; Coelho‐Silva, Juan L.; Weinhäuser, Isabel; Franca‐Neto, Pedro L.; Silveira, Douglas R.; Ortiz, César; Moreira‐Aguiar, Amanda; Lima, Marinus M.; Koury, Luisa C.; de Melo, Raul A.; Glória, Ana B.; Fagundes, Evandro M.; et al.
Summary: Although a growing body of evidence demonstrates that altered mtDNA content (mtDNAc) has clinical implications in several types of solid tumours, its prognostic relevance in acute promyelocytic leukaemia (APL) patients remains largely unknown. Here, we show that patients with higher‐than‐normal mtDNAc had better outcomes regardless of tumour burden. These results were more evident in patients with low‐risk of relapse. The multivariate Cox proportional hazard model demonstrated that high mtDNAc was independently associated with a decreased cumulative incidence of relapse. Altogether, our data highlights the possible role of mitochondrial metabolism in APL patients treated with ATRA.